Sleep Disorders and Subjective Well-Being in Portuguese Adults: Evidence from a Representative Study - Oliveira, Sara; Agostinis Sobrinho, Cesar; Martins, Silvana; Augusto, Cláudia; Araújo, Odete; Vieira, Teresa; Macedo, Ana Paula; Silva, Maria José; Rosário, Rafaela (Sleep Science, 2024)
Objective The quality and quantity of sleep affect people's well-being, as chronic sleep disorders are associated with social, physical, and psychological problems, as well as low self-reported life satisfaction. The present cross-sectional study examined the associations of sleep disorders with self-reported life satisfaction in Portuguese adults.Materials and Methods Data from a representative sample of the Portuguese population (14,341 participants, aged ≥ 18 years) extracted from the Sixth Portuguese National Health Survey was analyzed. Data on subjective well-being and sleep disorders was collected through a questionnaire, and multivariable regression models were performed to examine the associations between these variables, adjusted for potential confounders such as age, gender, level of schooling, degree of urbanization, and family income.Results Sleep disorders were negatively associated with self-reported life satisfaction. Having at least one sleep disturbance in the last two weeks was significantly associated with a 3-point decrease in life satisfaction: β = −3.0 (95% confidence interval = −3.2–−2.7).Discussion Among Portuguese adults, sleep disorders were associated with a decline in life satisfaction. The present study provides new evidence from a representative sample to support the promotion of good sleep hygiene intervention programs.
Keywords: adult; sleep disorders; motivation; happiness